Development and validation of an RP-HPLC method to compare the apoptotic activity of quercetin found in marketed dietary supplements - Erim, Ümit Can; Ayşit, Neşe (My University, 2024)
Quercetin is a ubiquitous bioactive flavonoid found in broad selection of dietary supplements. It has potential beneficial health effects and induces therapeutic activity in many diseases including different types of cancer. Quercetin exerts cytotoxic activity in cancer and induces apoptotic cell death. Albeit, each dietary supplement consists of impurities, which in turn diminish the biological activity of the quercetin. Herein, we extracted quercetin from 5 different marketed dietary supplements in tablet formulation and detected their quercetin content by developing and validating an RP-HPLC method. We further investigated the cytotoxic activity of quercetin and its role in apoptosis through mitochondrial pathway in MCF-7 and 4T1 breast cancer cell lines. Our findings demonstrated that the quercetin content in all formulations was less than the amount stated in the labeling information, nevertheless they exerted significant cytotoxic activities in breast cancer cells. We revealed that formulations with high quercetin content induced apoptosis through restoring the tumor suppression activity of p53 and activating downstream caspases, whereas the formulation with low quercetin content potentially induced non-apoptotic cell death. Our work illustrates the involvement of quercetin in apoptosis through the mitochondrial pathway in accordance with the quercetin content detected by the RP-HPLC.
Keywords: Apoptosis; Breast Cancer; Flavonoids; Method Validation; Quercetin; RP-HPLC; Supplement